Job satisfaction of healthcare workers in an armed conflict zone, Cusco, Peru, 2013 - Vera-Monge, Víctor (2015)
Job satisfaction is defined as a pleasurable or positive emotional state resulting from a subjective perception of the work experiences of the subject (1). Worker satisfaction in the performance of their duties plays a very important role in the quality of health care; therefore the measurement of job satisfaction is a necessary task. In Peru we have limited information on job satisfaction that presents health personnel in some areas experiencing armed conflict, one being the sector Kiteni Echarate district (adjacent to the VRAE - Valley of the Apurimac and Ene rivers) of the Province of the Convention in the region of Cusco (2).